Dynamics of Agrarian Systems and Land Use Change in North Vietnam. (6th October 2016) - Hanh, Han Quang; Azadi, Hossein; Dogot, Thomas; Ton, Vu Dinh; Lebailly, Philippe
Abstract: During the period of socio‐economic transformation initiated in the late 1980s by the political reform (Doi Moi) in Vietnam, the agrarian systems evolved considerably. In the region around the capital, where the process of industrialization, urbanization, and international integration has been accelerating, a number of questions about the sustainability of those agrarian systems have been raised. By diagnosing and analysing the dynamics of the agricultural systems in Vietnam from 1980 to 2010, this study aims to provide decision‐makers with some sectorial and territorial policy options that are able to authorize the sustainable development of agriculture and rural society in the new socio‐economic context. By applying a systematic approach, including the historical and adaptive approaches, this study shows how well farmers in the Hai Duong province have adapted to socio‐economic and institutional changes, notably by transforming part of their paddy farms into other agricultural land use purposes, such as fish ponds, animal buildings, vegetable fields, and fruit orchards. These rapid changes, however, do not move in a direction that improves the sustainability of agrarian systems. The results revealed that farm holders are now facing many technical and economic contradictions, whereas issues that arise from the land no longer are only related to agricultural purposes. Competition for different functions of land use are now emerging, along with the fragmentation of plots, an imperfect land market, and rising property values ​​are all emerging. The prospect of the sustainability of agricultural systems was also analysed under different scenarios, highlighting the complexity of policy options. Copyright © 2016 John Wiley & Sons, Ltd.